Impact of Cross-Age Peer Tutoring on Academic Performance in High School Mathematics - Alda Marsuki (Mauve Journal De Leardu, 2024)
The purpose of this examine is to determine the impact of move-age peer tutoring on high faculty mathematics academic performance. One of the blended-strategies approaches was employed, which concerned quantitative studies of pre- and publish-check preferences between the tutees (N=60) and qualitative information provided through interviews with tutors and tutees. The quantitative results show a significant increase in mathematics rankings after the schooling program (p < 0.01) supported by the way of regression and ANCOVA analysis that proved the independent influence of this system on publish-take a look at scores. Better confidence, conceptual knowledge and motivation among individuals are highlighted in qualitative information. The correlational analyses highlight the importance of arithmetic tension and attitudes to educational overall performance. The study advances the knowledge base on effective academic interventions, and peer tutoring is one of the approaches that should be used to beautify arithmetic acquiring knowledge in the excessive college environment.